International and comparative taxation: essays in honour of Klaus Vogel - Kirchhof, Paul (Series on international taxation, 2001)
Titelaufnahme ohne Lokalsatz
"This ed. contains the 16 English language contributions made to the original Festschrift": "Staaten und Steuern", Heidelberg 2000 ++ MAUB/spe
Keywords: Bibliografie; Aufsatzsammlung; Steuerrecht; Staatsrecht; Vogel, Klaus